Meaning and Relevance of Social Piety in Muslim Societies - Sa’dullah Sa’dullah; Risma Alkaromah; Winny Azwita Putri (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
It can be observed that the advancement of comprehension within specific communities often serves to illuminate the presence and significance of religious belief systems. This is evidenced by the presence of formal storefronts and religious rituals. Conversely, there is less appreciation for the application of universal religious teachings in the social context of community life. This prompted researchers to embark on a study. This research draws upon the texts of piety in the Qur'an, which are mentioned in various forms. In the form of nouns (isim), lafadz al-shālihāt, lafadz al-shālihūn/al-shālihīn, and lafadz shālihan. In addition, the verb form (fi'l) is derived from the root words shaluha and aslaha. This study employs a qualitative analysis approach, with content analysis used to examine the texts. These are descriptive and verbalistic in nature, drawn from the Qur'an and Hadith. To elaborate on the data, the author employs a variety of approaches, including philosophical, semantic, and sociological. The research findings present an exploration of the meaning of the matan, or content, of the verses of social piety, demonstrating the cohesion of the concept of piety as an expression of social awareness.